Large-Scale Synthesis of Vertically Aligned ZnO Hexagonal Nanotube-Rod Hybrids Using a Two-Step Growth Method - Kim, Seong Been; Kim, Sungwoong; Kwon, Sun Sang; Lee, Won Woo; Kim, Jin-Sang; Park, Won Il (WILEY, 2013)
Zn-polar (0001) surfaces are more chemically reactive than other surfaces of ZnO crystals and drive preferential anisotropic and asymmetric growth along the [0001] direction, which facilitates growth of c-axis oriented, one-dimensional ZnO nanostructures. Accordingly, capping the top (0001) surface of ZnO crystals can impede c-axis growth and thus serve to modulate growth habits. In this study, we generated vertically aligned ZnO hexagonal nanotube-rod (h-NTR) hybrids by modulating growth habits during a second-stage process. Electron microscopy studies revealed the formation of very thin (10-20nm) single-crystalline nanotube walls along the edges of underlying hexagonal rod tops capped with Si. In addition, spatially resolved investigation of ZnO h-NTR indicated an abrupt increase in the measured bandgap across rod-tube junctions, which was ascribed to a quantum confinement effect and Burstein-Moss effect of carriers within the very thin nanotube walls.
Keywords: SURFACE POLARITY; CATHODOLUMINESCENCE; NANOSTRUCTURES; NANORODS